Integration of Social and Behavioral Sciences (SBS) in Undergraduate Libyan Medical Education Programs (Razi Medical Journal, 2025)
Human health is influenced by multiple interacting biological, psychological, sociocultural, economic, and behavioral factors. Research in behavioral and social sciences informs physicians' approaches to prevention, diagnosis, and patient care. Competent physicians, therefore, require knowledge of society and human behavior to develop essential communication skills, professional conduct, self-awareness, ethical reasoning, and cultural understanding. Consequently, these Social and Behavioral sciences are integral to medical training. This cross-sectional study examines the current state of Social and Behavioral Sciences integration in Libyan medical education programs through a survey of 105 faculty members, curriculum developers, and administrators. Findings reveal strong recognition of SBS importance (84.6% rated it "very important"), yet inconsistencies in curriculum implementation, with 27.9% reporting no formal SBS inclusion. Teaching methods remain lecture-dominated (77.9%), and key challenges include insufficient faculty expertise (59.6%) and curriculum time constraints (40.4%). The study recommended the early curricular integration, faculty development, and enhanced experiential learning.
Keywords: Social and Behavioral Sciences, Undergraduate, Medical Education.